A Study of the Interaction Between Cucurbit[8]uril and Alkyl‐Substituted 4‐Pyrrolidinopyridinium Salts. Issue 1 (6th December 2018) - Xu, Weitao; Kan, Jinglan; Yang, Bo; Prior, Timothy J.; Bian, Bing; Xiao, Xin; Tao, Zhu; Redshaw, Carl
Abstract: The interaction between cucuribit[8]uril (Q[8]) and a series of 4‐pyrrolidinopyridinium salts bearing aliphatic substituents at the pyridinium nitrogen, namely 4‐(C4 H8 N)C5 H5 NRBr, where R=Et (g1), n ‐butyl (g2), n ‐pentyl (g3), n ‐hexyl (g4), n ‐octyl (g5), n ‐dodecyl (g6), has been studied in aqueous solution by 1 H NMR spectroscopy, electronic absorption spectroscopy, isothermal titration calorimetry and mass spectrometry. Single crystal X‐ray diffraction revealed the structure of the host–guest complexes for g1, g2, g3, and g5. In each case, the Q[8] contains two guest molecules in a centrosymmetric dimer. The orientation of the guest molecule changes as the alkyl chain increases in length. Interestingly, in the solid state, the inclusion complexes identified are different from those observed in solution, and furthermore, in the case of g3, Q[8] exhibits two different interactions with the guest. In solution, the length of the alkyl chain plays a significant role in determining the type of host–guest interaction present. Abstract : Can I have some pumpkin soup, please? In the host–guest complexes formed between cucurbit[8]uril and the alkyl‐substituted 4‐pyrrolidinopyridinium salts 4‐(C4 H8 N)C5 H5 NRBr (R=Et, n ‐butyl, n ‐pentyl, n ‐dodecyl), the orientation of the guest molecule changes with the length of R. Solid state structures are different to those observed in solution, and for R= n ‐pentyl, there are two different interactions between Q[8] and the guest.